MATHEMATICAL MODELING OF OVERTHRUSTING FAULT AS A CAUSE OF ANDALUSITE-KYANITE METAMORPHIC ZONING IN THE YENISEI RIDGE - Korobeinikov S.N.; Polyansky O.P.; Likhanov I.I.; Sverdlova V.G.; Reverdatto V.V. (My University, 2006)
Regional structural features of the Yenisei Ridge are traditionally displayed as a NW-trending linear system of tectonic sheets that are thrust over one another and separated by faults where collision of blocks occurs. As a result, low- and moderate-pressure series of regional metamorphism turn out to be juxtaposed. Moderate-pressure metamorphism related to collision is locally superimposed on low-pressure metamorphic rocks. Therefore, andalusite is progressively replaced with kyanite, and new mineral assemblages of moderate pressure and deformational microstructures are formed.
Keywords: Yenisei ridge